2022
DOI: 10.3390/ma15113800
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Ceramic Based Hip Implant Composites Using Hybrid AHP-MOORA Approach

Abstract: Designing excellent hip implant composite material with optimal physical, mechanical and wear properties is challenging. Improper hip implant composite design may result in a premature component and product failure. Therefore, a hybrid decision-making tool was proposed to select the optimal hip implant composite according to several criteria that are probably conflicting. In varying weight proportions, a series of hip implant composite materials containing different ceramics (magnesium oxide, zirconium oxide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In this investigation, it was observed that ranking of impregnation materials are in descending order as A-5 > Furthermore, the ranking results of the proposed entropy-TOPSIS methodology were compared to those of other common MCDM methodologies to validate its applicability. The ranking results obtained by the entropy-TOPSIS approach were compared with VIKOR (Visekriterijumska optimizacija kompromisno resenjemeaning) [47] , ARAS (Additive ratio assessment) [48] , GRA (Grey relation analysis) [49] , PROMETHEE II (Preference ranking organization method for enrichment evaluation II) [50] , MOORA (Multiple objective optimization on the basis of ratio analysis) [51] , COPRAS (Complex proportional assessment) [52] approaches and ranking results are given in Table 8 and Figure 4. Table 8 demonstrates that the alternative A-5 highest of all other alternatives and the alternative A-1 lowest when solved with all the methods.…”
Section: Resultsmentioning
confidence: 99%
“…In this investigation, it was observed that ranking of impregnation materials are in descending order as A-5 > Furthermore, the ranking results of the proposed entropy-TOPSIS methodology were compared to those of other common MCDM methodologies to validate its applicability. The ranking results obtained by the entropy-TOPSIS approach were compared with VIKOR (Visekriterijumska optimizacija kompromisno resenjemeaning) [47] , ARAS (Additive ratio assessment) [48] , GRA (Grey relation analysis) [49] , PROMETHEE II (Preference ranking organization method for enrichment evaluation II) [50] , MOORA (Multiple objective optimization on the basis of ratio analysis) [51] , COPRAS (Complex proportional assessment) [52] approaches and ranking results are given in Table 8 and Figure 4. Table 8 demonstrates that the alternative A-5 highest of all other alternatives and the alternative A-1 lowest when solved with all the methods.…”
Section: Resultsmentioning
confidence: 99%
“…The key difference between these methods lies in the algorithms bringing different-scale, often qualitative, data into a single normalized space and the subsequent choice of a metric inside it. Examples of MCDM can be found both in tribology [ 36 ] and medicine [ 37 , 38 , 39 ], as well as in other areas [ 40 , 41 ]. Recently, MCDM, based on interval estimates, has been developed.…”
Section: Data Interpretation—the Combined Ahp–extended Vikor Methodsmentioning
confidence: 99%
“…Despite the criticism, Saaty's original proposed Consistency Index (CI) is actively used in significant decision-making processes, as follows: quantum computing challenges in the software industry [37]; analysis of project benefits of solar energy collection and irrigation systems (supported by funds for the Sichuan Vanadium and Titanium Materials Engineering Technology Research Centre Project) [38]; for contractor assessment during project life cycles (supported by Al-Mansour Contracting Company for Contracts, the Ministry of Housing and Construction, Iraq, and the University of Baghdad) [39]; for access point selection in hybrid LiFi/WiFi networks [40]; for reinforcing doctor-patient communication (supported by the Ministry of Education of the Republic of Korea and the National Research Foundation of Korea) [41]; to evaluate sustainable healthcare systems [42]; for risk assessment of oil and gas pipelines hot work [43]; the evaluation of the emergency management capacity of resilient communities (funded by the Humanities and Social Sciences Project of the Ministry of Education) [44]; for the selection of the type of concrete and the method of its maintenance in dry, hot climate conditions (supported by the Poznan University of Technology-Polish Academy of Science) [45]; in changing the damming level of a small hydropower plant (co-financed within the framework of the Ministry of Science and Higher Education programme as "Regional Initiative Excellence") [46]; for the optimal design of ceramic-based hip implant composites [47]. In a review article covering usage from 1977 to 2022, the highest percentage of publications came from China, India, and Iran.…”
Section: Literature Reviewmentioning
confidence: 99%